Blast mitigation performance of a novel cladding–connector​ system - Zhang, Xuejian; Wang, Xiaojuan; Zhou, Hongyuan; Du, Xiuli; Zou, Hai-Lin; Song, Tianyi; Wang, Yonghui; Zhang, Hong (Thin-walled structures, 2023)
A novel cladding–connector system with excellent energy absorption capacity was proposed to protect vulnerable walls in frame structures subjected to blast load in the present study. The cladding–connector system was constructed by combining a sacrificial cladding consisting of an aluminum foam core sandwiched by two steel plates and four connectors made of corrugated steel tubes. On one hand, the cladding absorbed a considerable amount of blast energy. On the other hand, the connectors controlled the load transfer to the protected structure to certain specific pre-defined value. With this approach, both relatively high energy absorption and relatively low load transfer can be achieved simultaneously. Specifically, based on the quasi-static compression test on the connectors and the field blast test on the sacrificial cladding, the numerical model of the proposed system was established with ANSYS/LS-DYNA and validated with the test results. Then the deformation mode, energy dissipation, and load transfer of the cladding–connector systems with flexible or rigid connectors under various charge weights were numerically studied and compared. Results showed that the proposed cladding–connector​ systems could dissipate a considerable amount of energy under blast, in which the major part was dissipated by the cladding and the rest by the connectors. Particularly, compared to the cladding–connector system with rigid connectors, the cladding–connector system with flexible connectors exhibited superior performance in terms of energy absorption and load transfer, especially under intense blast. With the merits of excellent energy absorption, significant blast intensity reduction, and load shift from the vulnerable walls to the load-bearing components, the proposed cladding–connector system with flexible connectors was more promising to effectively protect the existing frame structures against blast. •A cladding–connector system is proposed to protect walls of frame structures subjected to blast.•The proposed system shifts the blast load applied on the wall to the load-bearing frame.•The system simultaneously realizes favorable energy absorption and load transfer control.•The system absorbs a considerable amount of energy in a designable manner.•The system reduces the transferred load intensity in a designable manner.